MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS V SDN 009 TERANTANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Ismanuria, Ismanuria (Aksara Public, 2017)
This research is motivated by the lack of ability to read aloud grade students of SDN 009 Terantang KamparKabupaten District Mining District of Kampar. This study aims to improve the ability to read aloud using the demonstration to improve the ability to read aloud the fourth grade students of SDN 009 Terantang Mining District of Kampar, which is carried out for 1 month. Subjects of this study is the fourth grade students of SDN 009 Terantang Mining District of Kampar regency, totaling 26 students, consisting of 8 female students and 18 male students in the academic year 2015-2016. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the research, the conclusion to this research is the students' skills in reading aloud increased. It is known from preliminary data the average value of 63.0. When viewed from the classical completeness, there are 19.2% of students (5 persons) who finished obtaining a minimum value of 70 (according to the standard KKM). However, after the implementation of the demonstration method, obtained an average value of 68.9 or completeness of 50% of students (13 people). Then in the second cycle, to reach an average value of 81.0 or completeness of 100%. Thus, this research is successful.